TRANSFORMASI METODE PENULISAN HADIS PASCA ABAD KE-4 (Upaya Membangun Kembali Warisan Ilmu dengan Takhrij dan Rijlul Hadis) - Najibur Rohman (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
Since the fourth century Hijri, the writing of hadith books underwent a significant transformation. Scholars no longer travelled long distances to collect traditions but instead focused on systematising and verifying existing traditions. They compiled books based on certain themes and checked the sanad and matan of the traditions, as seen in Mustakhraj by Abū Nu'aim and Rijālul Hadith by al-Jurjānī. These efforts reflect an attempt to preserve and disseminate hadith knowledge in a more structured manner. This study aims to answer two problems: 1). What was the method and writing of hadith books after the 4th century. 2). What are the definitions of takhrij and rijālul hadith books and examples of both books? This study uses a library research approach with a qualitative descriptive method. A literature review was conducted on classical books and primary sources to analyse the way post-4th century scholars organised and verified hadith. As well as other literature related to this study. The results showed that: 1. post-4th century scholars focused more on the method of preserving hadith by emphasising takhrij and rijul hadith. 2. takhrij serves to verify the sanad and matan of the hadith while rijlul hadis deals with the analysis of the narrators.